FAKTOR - FAKTOR YANG MEMPENGARUHI AUDIT DELAY PERUSAHAAN - Christin, Jesica; Sufiyati, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study was to examine how firm size, solvability, public ownership, audit committee, and accountant public firm's reputation affects audit delay in manufacturing companies listed in the Indonesia's Stock Exchange during the 2018-2020 period. Purposive sampling method was used to narrow down the samples to 154 companies. Multiple linear regression was used to process the data, which was done using the software Microsoft Excel 2016 and Econometric Views (Eviews) 12.0 Student Version. The results of this study shows that public ownership significantly affects audit delay, whilst firm size, solvability, audit committee and accountant public firm's reputation significantly does not affect audit delay.